1997
DOI: 10.1001/archsurg.1997.01430360029005
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Induces IκB-α and Prevents Stress-Induced Endothelial Cell Apoptosis

Abstract: Arsenite, an inducer of the heat shock response, decreased stress-induced endothelial cell apoptosis. The mechanism of this protection may include decreased nuclear factor kappa B activity or increased inducible heat shock protein 70 levels. Heat shock protein 70 may serve as a molecular marker to determine not only the phenotypic state of the cell but also the durability of protection afforded by heat shock. These data support the hypothesis that stress-induced changes in transcription factor activity and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
44
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 16 publications
11
44
0
Order By: Relevance
“…One hour after a nonlethal heat shock treatment, cells no longer responded to added cytokines, as evidenced by the significant reduction in p50/p65 DNA binding, and suppression of NF-Bdriven reporter enzyme activity. As was shown in this study and previously by others (3,8,29,30), cells after stress failed to phosphorylate and subsequently degrade IB␣, the result being a failure of p50/p65 to translocate to the nucleus and bind to and stimulate the expression of genes normally activated following cytokine stimulation.…”
Section: Discussionsupporting
confidence: 80%
“…One hour after a nonlethal heat shock treatment, cells no longer responded to added cytokines, as evidenced by the significant reduction in p50/p65 DNA binding, and suppression of NF-Bdriven reporter enzyme activity. As was shown in this study and previously by others (3,8,29,30), cells after stress failed to phosphorylate and subsequently degrade IB␣, the result being a failure of p50/p65 to translocate to the nucleus and bind to and stimulate the expression of genes normally activated following cytokine stimulation.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have used one or both of these cytotoxicity assays and/or the differential dye uptake assay in combination with other assay methods (Edwards and Tolkovsky, 1994;Hardwick et al;Hughes et al, 1996;Burger et al, 1999;Lizard et al, 1999;McGuinness et al, 1999;Sumitomo et al, 1999;DeMeester et al, 1997). However, none have used this specific combination of assays in evaluating apoptosis in breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Hernan dez-Presa et al 16 have also demonstrated NF-B activation in early atherosclerosis. Other studies have shown a critical role of NF-B activation in myocardial 26 and endothelial cell 17 apoptosis. Some studies have also shown NF-B as a proapoptotic signal in human endothelial cells.…”
Section: Lox-1 and Nf-b Signal Transductionmentioning
confidence: 91%
“…14,15 Previous studies have demonstrated that NF-B is activated in accelerated and in advanced atherosclerosis. 16 Recent studies show that NF-B activation plays a critical role in apoptosis 17,18 and that ox-LDL induces the activation of NF-B in fibroblasts and in endothelial and smooth muscle cells. 19 Accordingly, we hypothesized that (1) ox-LDL upregulates its own receptor, LOX-1; (2) ox-LDL-mediated apoptosis of cultured HCAECs is associated with the action of LOX-1; and (3) NF-B activation plays an important role in this process.…”
mentioning
confidence: 99%